1987
DOI: 10.1128/jb.169.9.4124-4127.1987
|View full text |Cite
|
Sign up to set email alerts
|

Overproduction of Escherichia coli integration host factor, a protein with nonidentical subunits

Abstract: Integration host factor (IHF) is a small, basic protein that is needed for efficient recombination of bacteriophage lambda, as well as for other host and viral functions. We have constructed strains in which the two subunits of IHF, encoded by the himA and hip genes of Escherichia coli, are expressed under the control of the lambda rho L promoter. Separate overexpression of himA and hip led to the production of unstable and insoluble peptides, respectively. In contrast, the overexpression of both genes conjoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
117
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(118 citation statements)
references
References 17 publications
1
117
0
Order By: Relevance
“…It has been reported before (Nash et al, 1987) Figure 1) of both subunits are thought to interact with the DNA via the minor groove (Yang and Nash, 1989) and are, therefore, good candidates for these specific contacts. In this paper, we have shown that an IHF fusion protein with two C-terminal regions of HimA binds much better to the DNA than a fusion protein with two C-terminal regions of HimD.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported before (Nash et al, 1987) Figure 1) of both subunits are thought to interact with the DNA via the minor groove (Yang and Nash, 1989) and are, therefore, good candidates for these specific contacts. In this paper, we have shown that an IHF fusion protein with two C-terminal regions of HimA binds much better to the DNA than a fusion protein with two C-terminal regions of HimD.…”
Section: Discussionmentioning
confidence: 99%
“…Kits for plasmid purification and DNase I footprinting were purchased from Quiagen and Pharmacia, respectively. gd resolvase (Hatfull et al 1989), calf thymus topoisomerase I (Strausfeld & Richter 1989), and E. coli IHF (Nash et al 1987) were purified as described. Purified E. coli Fis was a kind gift from G. Muskhelishvili and R. Kahmann.…”
Section: Enzymes and Reagentsmentioning
confidence: 99%
“…Wild-type and mutant proteins were purified from overexpressing bacteria, as described previously (15,16).…”
Section: Methodsmentioning
confidence: 99%